1989
DOI: 10.1017/s002202990002639x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the concentration of metabolites in milk from cows fed on diets supplemented with soyabean oil or fatty acids

Abstract: Cows were fed on diets supplemented with soyabean oil or soyabean fatty acids which in some cases were protected from rumen hydrogenation. The fatcontaining diets reduced the output of short-and medium-chain fatty acids in milk. Associated with this fall in short-and medium-chain fatty acids was a decrease in the concentration of 2-oxoglutarate and an increase in that of isocitrate and citrate. Protection of polyunsaturated fat from rumen hydrogenation had no significant effect. Milk yields were unaffected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 9 publications
3
15
0
Order By: Relevance
“…Faulkner, 1980;Faulkner and Pollack, 1989;Hurtaud et al, 1998 and2000;Rigout et al, 2002 and2003); in fairly good agreement with the present enzymatic-fluorometric determination, that is, mean 81 µM (P 1 to P 99 interpercentile = 5 to 330 µM, n = 3233).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Faulkner, 1980;Faulkner and Pollack, 1989;Hurtaud et al, 1998 and2000;Rigout et al, 2002 and2003); in fairly good agreement with the present enzymatic-fluorometric determination, that is, mean 81 µM (P 1 to P 99 interpercentile = 5 to 330 µM, n = 3233).…”
Section: Discussionsupporting
confidence: 89%
“…Marschke and Kitchen (1984) found from 20 to 570 µM (mean 220 µM; n = 188) glucose after centrifugation and precipitation of samples. Lemosquet et al (2004) found on average 480 to 580 µM; Rigout et al (2002) 430 to 570 µM; Hurtaud et al (1998 and2000) reported 720 to 830 µM and 510 to 650 µM, respectively; and Faulkner and Pollack (1989) 350 to 580 µM. Most of these studies are based on a relatively limited number of analyses and animals.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to previous results using sheep at a similar stage of lactation (e.g. Faulkner & Pollock, 1989;Faulkner & Martin, 1999), we found no reduction in peripheral resting insulin levels in the lactating animals, although this is in agreement with the findings of Vernon et al (1990) that lactation had no effect on pre-infusion levels of insulin in sheep. Ultimately, these differences in insulin levels found amongst the published studies in sheep comparing lactating and control animals may reflect varying levels of nutrition since this is thought to be a major factor in determining sensitivity to insulin (Metcalf & Weekes, 1990).…”
Section: Figuresupporting
confidence: 84%
“…A significant increase in citrate was also observed in goat's milk during 48 h of starvation (Chaiyabutr et al, 1981). The citrate content of milk is affected by the activity of the fatty acid synthesis in the mammary gland (Faulkner and Clapperton, 1981; Faulkner and Pollock, 1989). The synthesis of fatty acids in the mammary gland needs NADPH, which is produced when citrate is metabolized to α ‐ketoglutarate via isocitrate (Kirst et al, 1995).…”
Section: Feed Restrictionmentioning
confidence: 99%